HUBUNGAN DERAJAT PENYAKIT HIPERTENSI DENGAN TINGKAT KECEMASAN PADA KELOMPOK LANJUT USIA DI WILAYAH KERJA PUSKESMAS KAHAKITANG KECAMATAN TATOARENG - Femmy Lumi; Maria Terok; Freyjer Budiman (Politeknik Kesehatan Makassar, 2018)
Hypertension is a disease that is often experienced by the elderly and it becomes a global health issue that requires special attention because it can lead to major deaths in developed countries as well as developing countries. One of the risk factors of hypertension is anxiety. Anxiety is caused due to various circumstances such as worry, anxiety, fear, discomfort accompanied by various physical complaints and health problems. The purpose of this study was to analyze the relationship of degree of hypertension with anxiety level in elderly groupThe type of this research is analytical study with cross sectional, that have 95 population elderly and become 67 elder total sampel of characteristic inclusion. Data were collected using questionnaire and analyzed by using chi-square test. The Results Discussion have Degrees of hypertensive disease in elderly individuals (36%) were at mild and severe levels with moderate anxiety level in elderly (44.78%). The result of chi-square test using SPSS, P = 0,000 which is smaller than α = 0,05 meaning that there is a very significant relation on degree of hypertension with anxiety level in elderly groupBased on the results of research, the nurse will improve the elderly health by maintaining the promotion effort in the form of health counseling to the elderly group, empowering the elderly group and maintaining the psychological condition.